The effect and safety of constraint-induced movement therapy for post-stroke motor dysfunction: a meta-analysis and trial sequential analysis - Zhang, Jiaming; Xiao, Xianjun; Jin, Qizu; Li, Juan; Zhong, Dongling; Li, Yuxi; Qin, Yan; Zhang, Hong; Liu, Xiaobo; Xue, Chen; Zheng, Zhong; Jin, Rongjiang (Frontiers in Neurology, 2023)
Background: Rehabilitation of affected limbs in post-stroke motor dysfunction (PSMD) patients is difficult. Constraint-induced movement therapy (CIMT) as a neurorehabilitation technique, its effectiveness on PSMD after stroke is still controversial. Objective: This meta-analysis and trial sequential analysis (TSA) aimed to comprehensively evaluate the effect and safety of CIMT for PSMD. Methods: Four electronic databases were searched from their inception to Dec 31th 2022, to identify randomized controlled trials (RCTs) investigating the effectiveness of CIMT for PSMD. Two reviewers independently extracted the data, assessed the risk of bias and reporting quality. The primary outcome was a motor activity log for amount of use (MAL-AOU) and quality of movement (MAL-QOM). RevMan 5.4, Statistical Package for Social Sciences (SPSS) 25.0 and STATA 13.0 software were used for statistical analysis. The certainty of evidence was appraised with Grading of recommendations assessment, development, and evaluation (GRADE) system. We also performed the TSA to assess the reliability of the evidence. Results: A total of 44 eligible RCTs were included. Our results showed that CIMT combined with conventional rehabilitation (CR) were superior to CR in improving MAL-AOU and MAL-QOM score. The results of TSA indicated the above evidence was reliable. Subgroup analysis demonstrated that CIMT (≥ six hours per day or duration ≤ 20 days) combined with CR was more effective than CR. Meanwhile, both CIMT and modified CIMT (mCIMT) combined with CR were more efficient than CR in all stages of stroke. No severe CIMT-related adverse events occurred. Conclusions: CIMT may be an optional and safe rehabilitation therapy to improve PSMD. However, due to limited studies, the optimal protocol of CIMT for PSMD was undetermined, more RCTs are required for further exploration.